Penerapan Metode Dempster Shafer Pada Sistem Pakar Identifikasi Hama Tanaman Buah Naga Merah - Safitri, Hanifah Nur; Andreswari, Desi; Ginting, Sempurna Br (UNIB Press, 2025)
Red dragon fruit is a type of fruit that has bioactive components such as flavonoids, phenolics, betacyanins and anthocyanins. Red dragon fruit has a distinctive combination of flavors, namely sweet, sour and refreshingly savory. Apart from that, red dragon fruit also has several health benefits so this fruit is liked by many people. However, a lack of knowledge in maintaining red dragon fruit from pest attacks can cause the growth of red dragon fruit to be less than optimal and result in crop failure. Therefore, an expert system for identifying red dragon fruit pests is needed to minimize the risk of crop failure. The use of an expert system in identifying red dragon fruit pests by applying the Dempster Shafer method can determine the appropriate treatment thereby reducing the percentage of crop failure. The Dempster Shafer method is used to determine the level of certainty of a symptom and provide an accurate level of confidence. The results of this expert system test show that the identification results are close to the truth from an expert using 9 types of pests and 24 symptoms. The resulting accuracy level has a percentage of 100%. Keywords: Red Dragon Fruit, Expert System, Dempster Shafer Method